2000 IEEE International Conference on Acoustics, Speech, and Signal Processing. Proceedings (Cat. No.00CH37100)
DOI: 10.1109/icassp.2000.859152
|View full text |Cite
|
Sign up to set email alerts
|

GSM speech coding and speaker recognition

Abstract: This paper investigates the influence of GSM speech coding on text independent speaker recognition performance. The three existing GSM speech coder standards were considered. The whole TIMIT database was passed through these coders, obtaining three transcoded databases. In a first experiment, it was found that the use of GSM coding degrades significantly the identification and verification performance (performance in correspondence with the perceptual speech quality of each coder). In a second experiment, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Experiment 2, Simulation 1 testing and training the small source/microphone distance in Room 1 there are not room parameters significant levels of room reverberation and hence SI accuracy stage where speed is not a concern and storage requirements for speaker models are relatively small. The proposed method also requires N times as many likelihood calculations in the test stage [compare (5) with (4)] which will increase identification time. tion, the frequency with which the training rooms were assoTraining 2 (4.0, 3.0, 3.5) ciated with the identified speaker were tabulated and are given Training 3 (4.0, 3.0, 3.5)…”
Section: Test Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiment 2, Simulation 1 testing and training the small source/microphone distance in Room 1 there are not room parameters significant levels of room reverberation and hence SI accuracy stage where speed is not a concern and storage requirements for speaker models are relatively small. The proposed method also requires N times as many likelihood calculations in the test stage [compare (5) with (4)] which will increase identification time. tion, the frequency with which the training rooms were assoTraining 2 (4.0, 3.0, 3.5) ciated with the identified speaker were tabulated and are given Training 3 (4.0, 3.0, 3.5)…”
Section: Test Signalmentioning
confidence: 99%
“…Because it is unrealistic to know in advance packet due to speech coding and distortions due to packet loss. In loss rates and somewhat difficult to accurately measure loss [5], the authors passed TIMIT signals through Global System rates, training channels can only approximate test channels. for Mobile (GSM) speech coders and measured SI accuracy Nevertheless, it was found that if a set of packet loss models of approximately 60% (40% lower compared to TIMIT).…”
Section: Introduction Weighted Mixture Of W Gaussian Pdfsmentioning
confidence: 99%
“…where Q nm denotes 4 bits of the channel quality identifier (CQI) value and A nm denotes the current channel utilization status [11].…”
Section: Fig1 Radio Resources Grid Of Lte Networkmentioning
confidence: 99%
“…Speaker recognition performance with GSM coded speech has found to improve and become comparable to recognition on the original speech with the use of speech coding parameters for recognition e.g., cepstral coefficients derived from the LP spectrum [5] or Line Spectral Frequencies (LSFs) [6]. Similarly, speech recognition performance was also found to improve when using cepstral coefficients derived from speech codec parameters, compared to recognition on the decoded speech [7] [8].…”
Section: Introductionmentioning
confidence: 99%